PRINSIP AKUNTABILITAS DAN TRANSPARANSI YAYASAN DALAM RANGKA MENCEGAH PRAKTIK PENCUCIAN UANG (MONEY LAUNDERING) - DWI CESARIA SITORUS; BISMAR NASUTION; WINDHA WINDHA (Universitas Sumatera Utara, 2013)
Money laundering crime should be prevented as early as possible in order to create a country with a moral society. The practice of money laundering can occur both through banking and non-banking institutions, such as insurance and foundations. With the foundation, all the desires of social, humanitarian, and religious people can be realized in an institution that has been recognized and accepted its existence. In principle there is a foundation of accountability and transparency that has an important role to prevent money laundering. There are some basic issues to be discussed in this thesis writing. A primary issue is how the practice of money laundering in Indonesia, how the existence of the foundation in the Indonesian legal system, and how the application of the principles of accountability and transparency of foundations in order to prevent money laundering. The method used in the thesis writing is done with normative juridical approach is to perform an analysis of the problems with the approach to the principles of law and refers to the legal norms contained in the legislation. The study was conducted with an emphasis on the data library by library research, which conducts research using materials from a variety of reading materials such as legislation, books, magazines, and the Internet. The principle of accountability and transparency is needed in conducting business foundation itself. This is in order to prevent money laundering practices that function Foundations of Law No. 16 of 2001 jo. Law No. 28 of 2004 and Law No. 8 of 2010 Concerning the Prevention and Suppression of Money Laundering can be carried out in accordance with these provisions. Key words : Akuntabilitas, Transparansi, Yayasan, Pencucian Uang